Preferred Drinking Water Sources and Waterborne Infections Among Households in a Rural Community in Anambra State, South East, Nigeria (West African Journal on Sustainable Development, 2024)
Background: The global demand for freshwater is increasing at an alarming rate, outpacing population growth. Access to safe water is a critical sustainable development issue, with 2.1 billion people worldwide and over half of the population in developing countries lacking a "safely managed" water supply. This study aimed to investigate the microbiological quality of preferred drinking water sources and its association with waterborne infections (WBIs) among households in Ebenebe, a rural community in Anambra State, Nigeria.Methodology: A cross-sectional descriptive survey and laboratory analysis were conducted among 504 households. Data on preferred drinking water sources, determinants, and symptoms of WBIs were collected using a questionnaire. Water and faecal samples were collected from randomly selected household members for laboratory analysis.Results: The findings revealed that borehole water (74%) was the most commonly accessed and preferred drinking water source. Borehole water samples contained 74.3% of all isolated bacteria, while spring and lake samples had the least (2.9%). Escherichia coli (295, 19%) was the most frequently detected bacterium, with no parasites seen. Faecal analysis showed that 427 respondents (85%) had WBIs, with those aged 15-64 years (332, 77.8%) and females (253, 59.3%) being the most affected. Helminthes were the most frequently detected parasite (203, 93%), and hookworm (81, 37%) was the most common parasite ova seen. Overall, E. coli was the most frequently isolated microorganism. However, the association between preferred drinking water sources and WBIs was not statistically significant.Conclusion: The preferred drinking water of households in Ebenebe contained pathogenic organisms capable of causing WBIs and diseases. Therefore, health education on user-friendly, point-of-use filtration and disinfection methods is recommended to improve the water quality and reduce the risk of WBIs and diseases.
Keywords: drinking water; waterborne infections; Ebenebe; Anambra State; Nigeria